THE EFFECT OF USING LISTENING-READING-DISCUSSION (LRD) STRATEGY ON STUDENTS UNDERSTANDING OF READING NARRATIVE TEXT AT MTS PALASA - Cindy; Andi Muhammad Dakhalan; Dzakiah, Dzakiah (English Tadris Department, Tarbiyah and Teacher Training Faculty, Datokarama State Islamic University Palu, 2022)
The reading comprehension of grade IX students of MTs Palasa is still low, especially in reading narrative texts. so that the researcher was motivated to discuss the thesis entitled